AB1320 Discriminating sarcopenia in community-dwelling older women with high frequency of overweight/obesity: Results from the sÃo paulo ageing & health study (SPAH). (23rd January 2014) - Domiciano, D.S.; Figueiredo, C.P.; Lopes, J.B.; Caparbo, V.; Takayama, L.; Bonfa, E.; Pereira, R.M.R.
Abstract : Background: The most widely used criteria for sarcopenia, byratio between the appendicular skeletal muscle mass(ASM) and height squared(h 2 ) (Baumgartner et al ) has the disadvantage to underestimate the prevalence in overweight/obese people, whereas another criteria considers ASM adjusted for total fat mass(Newman et al ). Objectives: Since prevalence of overweight/obesity is a growing public health issue in the world population, including older people, the aim of this study was to evaluate the prevalence and risk factors associated with sarcopenia, according to these two criteria in older women. Methods: A total of 611 community-dwelling women, aged over 65 years, were evaluated by specific questionnaire including clinical data. Body composition and bone mineral density were evaluated by DXA. Laboratory tests were also performed. According to Baumgartner's, sarcopenia was defined when the relative skeletal muscle mass index (ASM/h 2 ) was less than 5.45 kg/m 2 . ASM adjusted for fat criteria was based on linear regression used to model the association between ASM on height and fat mass. The residuals from linear regression models were used to identify those individuals whose amount of ASM was lower than expected for a given amount of fat mass. The equation resultant from the model was ASM (kg) = -14.51+ 17.27 X height (m) + 0.20 X fat mass (kg). The 20th percentile of the distribution of the residuals was used as sarcopenia cutpoint, which corresponded to -1.45 in our population. Logistic regression models were used to identify risk factors related to ASM/h 2 and ASM adjusted for fat criteria. Results: The prevalence ofoverweight/obesity (BMI>24.9 kg/m 2 ) in this community-dwelling older womenwas high (74.3%). The frequency of sarcopenia was significantly lower using ASM/h 2 (3.7%) than ASM adjusted for fat(19.9%) criteria ( P <0.0001). Of note, less than 5%(1/23) of those classified as sarcopenic by ASM/h 2 had overweight/obesity, whereas 60%(74/122) of sarcopenic women by ASM adjusted for fat had this complication. Risk factors, after adjustments for age, were identified to be distinct in the two groups. Using ASM/h 2, risk factors observed in regression models were femoral neck T-score (OR=1.90; 95%CI 1.06-3.41; P =0.03) and current alcohol intake(OR=4.13, 95%CI 1.18–14.45, P =0.02). In contrast, we have identified that creatinine (OR=0.21; IC95% 0.07-0.63; P =0.005) and White race(OR=1.81; IC95% 1.15-2.84; P =0.01) had significant association with sarcopenia in the group defined by ASM adjusted for fat criteria. Conclusions: In women with overweight/obesity, ASM adjusted for fat criteria seems to be more appropriate for sarcopenia diagnosis. This finding has relevant public health implications taking into consideration the distinct risk factors identified herein and the high prevalence of overweight/obesity in older women. References: Baumgartner RN, Koehler KM, Gallagher D, Romero L, Heymsfield SB, Ross RR et al. Epidemiology of sarcopenia among the elderly in New Mexico. Am J Epidemiol 1998;147:755-63. Newman AB, Kupelian V, Visser M, Simonsick E, Goodpaster B, Nevitt M et al. Health ABC Study Investigators. Sarcopenia: alternative definitions and associations with lower extremity function. J Am Geriatr Soc 2003;51:1602-9 Disclosure of Interest: None Declared